2020
DOI: 10.1186/s42836-020-0024-2
|View full text |Cite
|
Sign up to set email alerts
|

Can urinary CTX-II be a biomarker for knee osteoarthritis?

Abstract: Background: Early diagnosis of knee osteoarthritis (OA) remains a diagnostic challenge. Urinary C-terminal crosslinked telopeptide of type II collagen (urinary CTX-II) is one of the potential OA biomarkers. However, conclusive evidence regarding the use of this biomarker as a tool for early diagnosis is still lacking. The purposes of this study were to compare urinary CTX-II levels in patients with knee OA and in healthy controls, to evaluate the correlation between urinary CTX-II levels, radiographic severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
4
8
1
Order By: Relevance
“…In our study, the urinary CTX-II levels showed an inverse correlation with some of the KOOS domains scores, showing that a higher level of knee-related problems was reflected in a higher level of urinary CTX-II. This is in accordance with previous studies using the patient-reported outcome of WOMAC index ( 38 ). This observed correlation may explain the beneficial effect of GSM on both urinary CTX-II and the KOOS domains, while COMP levels were not affected.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, the urinary CTX-II levels showed an inverse correlation with some of the KOOS domains scores, showing that a higher level of knee-related problems was reflected in a higher level of urinary CTX-II. This is in accordance with previous studies using the patient-reported outcome of WOMAC index ( 38 ). This observed correlation may explain the beneficial effect of GSM on both urinary CTX-II and the KOOS domains, while COMP levels were not affected.…”
Section: Discussionsupporting
confidence: 93%
“…The lack of effect of GSM on urinary CTX-II could be due to high levels of urinary CTX-II at baseline (571.6 ± 415.6 ng/mmol Cr), which were higher than the values from a previous study (511.92 ± 486.21 ng/mmol Cr) using the same ELISA kit in elderly females with knee OA (age 64.45 ± 10.6 years) (38). Thus, due to high levels of urinary CTX-II, a notable reduction may not have been detected after 12 weeks of GSM treatment, and longer duration may result in a more significant effect.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In this study, we were only able to measure the concentration of sCOMP, sPIICP, and sHA despite other biomarkers such as PIIANP [ 39 ], C-telopeptide of type II collagen (CTX-II) [ 67 , 71 ], and synovial cytokines [ 72 ], and others [ 19 ] have been reported. Moreover, there was a statistical limitation because the relationship between each of the three biomarkers and the severity of OA and other OA risk factors was assessed using two tests, linear regression analysis, and Spearman’s Correlation test.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sympathectomy reduced the degradation of type II collagen as indicated by reduced serum CTX-II levels compared to WT DMM mice. CTX-II was also demonstrated to be higher in spontaneous osteoarthritic mice (Watari et al 2011) and in knee-OA patients compared to healthy ones (Arunrukthavon et al 2020). The increased CTX-II level in WT mice after 4 weeks suggests that type II collagen degradation begins at the early stage of OA development.…”
Section: The Protective Effect Of Sympathectomy In Oa Cartilagementioning
confidence: 95%